The study on job satisfaction at Jabatan Pengankutan Jalan (JPJ) Sungai Petani / Nur Aina Afiqah Abd Halim ... [et al.] - Abd Halim, Nur Aina Afiqah; Md Elias, Nur Hidayah (2018)
This chapter focused on the background of the study which titled "The Study on Job Satisfaction at Jabatan Pengangkutan Jalan (JPJ) Sungai Petani”. This chapter consist of research background followed by problem statement, research questions, research objectives, scope of study, significant of study and the definition of term and concept use in this study.